Pengembangan LMS Berbasis Project-Based Learning Dengan Integrasi Gamifikasi Untuk Meningkatkan Kemampuan Kognitif Pada Mata Pelajaran Basis Data (Studi Kasus: Siswa Kelas XI RPL SMK 17 Agustus 1945 Surabaya) - Nuril Aliya Al Aini; Martini Dwi Endah Susanti (CV. SINAR HOWUHOWU, 2026)
This study aimed to develop the GamaBase Learning Management System (LMS) based on Project-Based Learning (PjBL) integrated with gamification to improve students’ cognitive abilities in Database learning. The LMS was developed using the ADDIE model, consisting of the analysis, design, development, implementation, and evaluation stages. Its effectiveness was evaluated using a quasi-experimental method with a Nonequivalent Control Group Design involving 60 eleventh-grade Software Engineering students at SMK 17 Agustus 1945 Surabaya, divided into an experimental group and a control group. Data were collected through expert validation, functional system testing, and cognitive ability assessments using pretests and posttests. The results showed that the GamaBase LMS met the criteria for being highly feasible as a learning medium. The analysis of cognitive improvement showed that the experimental group obtained a mean N-Gain score of 0.778, categorized as high, while the control group obtained a mean N-Gain score of 0.498, categorized as moderate. The Mann-Whitney test showed a significant difference in cognitive improvement between the experimental and control groups, with a significance value of p < 0.001. Therefore, the GamaBase LMS based on PjBL integrated with gamification was effective in improving students’ cognitive abilities in Database learning, particularly higher-order thinking skills involving analyzing, evaluating, and creating.